Translation Technique Of English To Indonesian Subtitle In Doraemon Stand By Me Movie - Fitria, Tira Nur, Dr. Anam Sutopo, M.Hum, Dr. Dwi Haryanti, M.Hum (Universitas Muhammadiyah Surakarta, 2015)
This objectives of the research are to classify the types of translation technique from English to Indonesian subtitle, to determine the most dominant type of translation technique and to describe the translation quality of English to Indonesian subtitle of Doraemon "Stand By Me" movie in the term of accuracy, acceptability and readability. This research is descriptive qualitative method. Data of this research are utterances or sentences in subtitle movie of bilingual edition, both English and Indonesian. While, the source data of this research is "Stand By Me" Doraemon movie. The writer used two kinds of data source, they were document and informant. In analyzing the data, the writer used comparison method to compare between the SL and TL that were analyzed. The result of this research shows that 1) there are eleven type of translation techniques, they are: First, 1) Adaptation (112 data or 10,28 %), 2) Amplification (80 data or 7,35 %), 3) Borrowing, (93 data or 8,54%), 4) Calque (30 data or 2,75 %), 5) Compensation (4 data or 0,37 %), 6) Discursive Creation ( 2 data or 0,18 %), 7) Established Equivalence (296 data or 27,18 %), 8) Literal Translation (276 data or 25,34 %), 9) Modulation (48 data or 4,41%), 10) Reduction (235 data or 21,58 %), and 11) Transposition (199 data or 18,27 %). Second, the most dominant type of translation technique is Established Equivalence. It has higher frequency data (297 data or 27,27 %). Third, the result shows that translation quality assessment, in translation accuracy, the higher percentage is accurate. There are 239 data or 66,38 %. In translation acceptability, the higher percentage is acceptable. There are 233 data or 64,72 %. In translation readability, the higher percentage is readable. There are 260 data or 72,22 %. Therefore, it can be concluded that the translation quality of "Stand By Me" Doraemon movie is accurate, acceptable and readable. Key Words: Translation, Translation Technique, Accuracy, Acceptability, Readability.